Impact of the COVID-19 pandemic on children's social, emotional, and moral development: A systematic literature review - Zaharah binti Osman, Abdul Halim bin Masnan, Anis Norma binti Mohamad Jaafar, Romarzila binti Omar, Amelia binti Mohd Noor (Tanjung Malim, 2024)
Impact of the COVID-19 pandemic on children's social, emotional, and moral development: A systematic literature review by Zaharah binti Osman, Abdul Halim bin Masnan, Anis Norma binti Mohamad Jaafar, Romarzila binti Omar, Amelia binti Mohd Noor